PENGARUH PENGENDALIAN INTERNAL, INTERNAL LOCUS OF CONTROL, DAN BYSTANDER EFFECT TERHADAP KECURANGAN PADA LEMBAGA PERKREDITAN DESA DI KECAMATAN KINTAMANI - Ni Putu Dian Ganesuari Dian; I Made Pradana Adiputra (Universitas Pendidikan Ganesha, 2023)
This study aims to determine the effect of internal control, internal locus of control and bystander effect on fraud. This research is a type of quantitative research with a total of 117 respondents from Village Credit Institutions in the Kintamani District. Samples were selected using criteria with purposive sampling technique. The data used is primary data obtained from distributing questionnaires directly to respondents. The data analysis technique used was multiple linear regression analysis which was processed using SPSS version 20. The results showed that internal control had a negative and significant effect on fraud, internal locus of control had a negative and significant effect on fraud, and bystander effect had a positive and significant effect on fraud. The coefficient of determination test shows that the internal control, internal locus of control and bystander effect can explain fraud by 37.1 percent. Based on the results of these studies, the recommendations for improvement in this study are focused on adding other independent variables, such as suitability of compensation and management morality, so that the results of the research will be able to increase the value of the coefficient of determination.